1998
DOI: 10.1111/j.1600-0722.1998.tb02167.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental role of PTHrP in murine molars

Abstract: Although PTHrP is produced in multiple fetal tissues, its precise physiological functions have yet to be clearly elucidated. The present study was undertaken to elucidate the biological role of PTHrP in the development of tooth. In rat tooth germs, the PTHrP and its receptor genes were expressed in the enamel organ and dental mesenchyme, respectively. When mouse tooth explants were cultured with antisense oligodeoxyribonucleotides (ODN) against mouse PTHrP mRNA in serum‐free medium, an invasion of bone tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 2 publications
2
16
0
1
Order By: Relevance
“…Dans des études sur les rongeurs, il a été mis en évidence l'importance de l'expression élevée de PTHR-1 et PTHrP au cours du développement dentaire [15,27]. D'autres études chez des souris soutiennent également le rôle important de la PTHrP et de la PTHR-1 dans le développement du squelette et leur association avec l'ostéoarthrite [23,24], il serait intéressant que des études de plus grande cohorte portent sur le lien de causalité entre PTHR-1 et l'ostéoarthrite.…”
Section: Discussionunclassified
“…Dans des études sur les rongeurs, il a été mis en évidence l'importance de l'expression élevée de PTHR-1 et PTHrP au cours du développement dentaire [15,27]. D'autres études chez des souris soutiennent également le rôle important de la PTHrP et de la PTHR-1 dans le développement du squelette et leur association avec l'ostéoarthrite [23,24], il serait intéressant que des études de plus grande cohorte portent sur le lien de causalité entre PTHR-1 et l'ostéoarthrite.…”
Section: Discussionunclassified
“…Extensive research in the past decade has revealed PTHrP and/or PTHR1 expressions and their contribution to tooth development in both rodent and human (Beck et al, 1995;Lee et al, 1995;Tenorio and Hughes, 1996;Liu et al, 1998;Lundgren et al, 1998;Philbrick et al, 1998;Kitahara et al, 2002;Wysolmersky et al, 2001;Comier et al, 2003). Recently, Calvi and colleagues showed PTHR1 expression and suggest its possible function in the odontoblasts of fetus and neonates of continuously PTHR1 expressing transgenic mice (Calvi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In tooth development, PTHrP is known to express in enamel epithelia (Beck et al, 1995;Lee et al, 1995;Liu et al, 1998), while its receptor (PTH/PTHrP receptor 1 or PTHR1) is expressed in cementoblasts (Tenorio and Hughes, 1996), dental papilla (Lee et al, 1995;Liu et al, 1998), and odontoblasts (Lundgren et al, 1998;Calvi et al, 2004). In addition, functional studies have revealed that PTHrP is required for tooth eruption (Schipani et al, 1997;Phibrick et al, 1998;Kitahara et al, 2002), and recently Calvi and colleagues revealed, using continuously PTHR1 expressing transgenic mice, the critical role of the receptor in early dentinogenesis in fetal and neonatal mice (Calvi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Asterisk(s): significantly different from control ( * : p < 0.05, * * : p < 0.01). Tenorio and Hughes, 1996;Liu et al, 1998;Calvi et al, 2004), it is striking but considered extrinsic increase of PTHrP does not affect the generation and maturation of those cells in this HHM model using matured animals.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of tooth development, PTHrP is known to express in enamel epithelia (Beck et al, 1995;Lee et al, 1995;Liu et al, 1998), while PTH/PTHrP receptor 1 (PTHR1) in cementoblasts (Tenorio and Hughes, 1996), dental papilla (Lee et al, 1995;Liu et al, 1998) and odontoblast (Lundgren et al, 1998;Calvi et al, 2004). In addition, functional studies revealed the fact that PTHrP expression was required for tooth eruption (Schipani et al, 1997;Philbrick et al, 1998;Kitahara et al, 2002), and recently Calvi and colleagues revealed, with continuously PTHR1 expressing transgenic mice, that critical role of this receptor on early odontogenesis in fetus and neonatal mice (Calvi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%